2018
DOI: 10.1039/c7cc08548f
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired design of a hybrid bifunctional enzymatic/organic electrocatalyst for site selective alcohol oxidation

Abstract: This work combines the thermostable alcohol dehydrogenase D (AdhD) from Pyrococcus furiosus and the organic electrocatalyst TEMPO to create a bifunctional catalyst that selectively oxidizes primary and secondary alcohols. The active sites function independently, can be switched on by changing reaction conditions, and can selectively oxidize a mixture of 1- and 2-butanol. The NAD-dependent enzyme catalyses the secondary alcohol oxidation at a rate 3-fold faster than the primary alcohol, while the covalently att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Some very good literature reports on the selectivity in this type of system are available. For example, lignin and lignin models have been selectively oxidized by a TEMPO derivative at the β-O-4 linkages in work by multiple groups [37][38] In other work, a bifunctional TEMPO catalyst that also selectively oxidizes alcohols was reported [39] in addition to an earlier report of computational model. [40] The general mechanism of alcohol oxidation by TEMPO is affected by many factors including the stability of the oxoammonium cations and the oxidation potentials.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Some very good literature reports on the selectivity in this type of system are available. For example, lignin and lignin models have been selectively oxidized by a TEMPO derivative at the β-O-4 linkages in work by multiple groups [37][38] In other work, a bifunctional TEMPO catalyst that also selectively oxidizes alcohols was reported [39] in addition to an earlier report of computational model. [40] The general mechanism of alcohol oxidation by TEMPO is affected by many factors including the stability of the oxoammonium cations and the oxidation potentials.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Electrochemistry is a green and sustainable technology that has been widely applied in bioanalysis, synthetic chemistry, and energy interconversion. Merging biocatalysis with alternative catalytic techniques such as electrocatalysis or photocatalysis further expands the scope of biocatalytic synthesis by accessing higher reactivity and selectivity or unlocking novel enzymatic cascades or un-natural reactivities. In many examples of bioelectrocatalytic reactions, terminal oxidants or reductants have been demonstrated to be completely replaceable with electricity, offering enormous potential in the efficient manufacture of pharmaceuticals and fine chemicals. , Herein, we disclose the development of the first bioelectrocatalytic aerobic oxidation of alcohols via electrochemical activation of GOase. , We have successfully applied this new synthetic reaction to desymmetrizing oxidation of 2-ethynylglycerol, a key step in biocatalytic cascade synthesis of islatravir, and expanded the synthetic scope to a range of alcohols. Spectroscopic and electrochemical studies have revealed the redox properties of the specifically engineered GALO-104 (GOase Rd10BB in ref ) as well as the proton-coupled electron-transfer (PCET) mechanism of GOase oxidation by the mediator.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Herein, we disclose the development of the first bioelectrocatalytic aerobic oxidation of alcohols via electrochemical activation of GOase. 17,18 We have successfully applied this new synthetic reaction to desymmetrizing oxidation of 2-ethynylglycerol, a key step in biocatalytic cascade synthesis of islatravir, and expanded the synthetic scope to a range of alcohols. Spectroscopic and electrochemical studies have revealed the redox properties of the specifically engineered GALO-104 (GOase Rd10BB in ref 3) 19 as well as the proton-…”
Section: ■ Introductionmentioning
confidence: 99%
“…The use of mediators in electrochemical reactions has a long history in electrosynthesis, including bioinspired mediators such as quinones and NAD+, as well as nitroxyls . Nitroxyls can function both as alcohol oxidation electrocatalysts and mediators that operate by hydrogen atom abstraction (e.g., Cu-coordinated alcohols). , Ferrocene, flavins, and polypyridyl complexes of ruthenium and osmium mediate the transfer of electrons from glucose oxidases to anodes in glucose-detection technologies and fuel cells. ,, Typically, mediators are two-electron/two-proton shuttles or agents that mediate electron transfer.…”
Section: Introductionmentioning
confidence: 99%